Kajian Aspek Protein Turnover Tubuh pada Ayam Kedu Periode Pertumbuhan - N Suthama (Media Peternakan, 2006)
Growth rate can be clarified based on body protein turnover in Kedu chicken given improved diet. Protein turnover is estimated according to the difference of protein synthesis and breakdown rates using the excretion of -methylhistidine (Nτ–MH) as an indicator. One hundred forty four (144) birds of non-black Kedu chicken of 2 weeks old purchased from the farmer group at Kedu village were used as the experimental animals. The birds were then reared until 16 weeks old (4 months). Experiment was started at 4 weeks old by dividing the birds into 3 groups according to the tested diets. Diet 1 (R1): farmer's diet formula consisting of yellow corn (40%), rice bran (40%) and concentrate (20%). Diet 2 (R2): simple modification of R1, added with CaCO3 and premix. Diet 3 (R3): new formula by improving nutritional content. The present experiment was arranged in a completely randomized design with 3 treatments and 6 replications (8 birds each). Data of feed consumption, body weight gain, feed conversion ratio, (Nτ–MH) excretion, rates of protein synthesis (Ks) and of protein degradation (Kd) were statistically analyzed by analysis of variance and continued to Duncan test when the treatment effect was significant (P < 0.05). (Nτ–MH) and nitrogen were measured from the totally collected excreta at the last week of the experiment. Body weight gain, muscle protein mass, nitrogen retention and Ks in R3 increased significantly (P < 0.05) as compared to those in R1. However, feed conversion ratio and (Nτ–MH) excretion in R3 decreased and significantly lower than those in R1. Feed consumption and Kd indicated the same values in all treatments. Improvement of dietary quality and nutritional content brought about the increase in growth rate and muscle protein mass, even though at a slow rate. This phenomenon was supported by the acceleration rate of Ks at a slow rate as well, with unchangeable rate of Kd. Feed utilization was not efficient since the value of feed conversion ratio was categorized high, ranging from 2.9 to 3.3. Key words: diet, growth , protein turnover, Kedu chicken